Buyer power and price discrimination: The case of the UK care homes market - Ruth Hancock; Morten Hviid (University of Essex, Institute for Social and Economic Research (ISER), 2010)
UK Local Authorities purchase care home places on behalf of a large group of people following a means test of their income and wealth. All other buyers of care home services are atomistic. The care home market is characterised by a large number of small providers. Local authorities may thus have buyer power. We show that any abuse of this buyer power may lead to some people, the squeezed middle not being served. We quantify the size of the squeezed middle and assess the implications of the form of the means test for local authorities' ability to exercise buyer power.
Keywords: I11; I19; I31; 330; buyer power; care home market; long term care financing; Gesundheitswesen; Gesundheitskosten; Pflegedienst; Angebot; Marktmechanismus; Großbritannien